2003
DOI: 10.1128/mcb.23.23.8878-8889.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Type-Specific Activation of PAK2 by Transforming Growth Factor β Independent of Smad2 and Smad3

Abstract: Transforming growth factor ␤ (TGF-␤) causes growth arrest in epithelial cells and proliferation and morphological transformation in fibroblasts. Despite the ability of TGF-␤ to induce various cellular phenotypes, few discernible differences in TGF-␤ signaling between cell types have been reported, with the only well-characterized pathway (the Smad cascade) seemingly under identical control. We determined that TGF-␤ receptor signaling activates the STE20 homolog PAK2 in mammalian cells. PAK2 activation occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
162
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(176 citation statements)
references
References 47 publications
(62 reference statements)
11
162
0
3
Order By: Relevance
“…The R-Smad/Smad4 complex subsequently translocates to the nucleus where it can function as a comodulator of transcription (Ten Dijke et al, 2002;Shi and Massagué, 2003). In addition to the aforementioned Smad-dependent pathways, Smad-independent responses have also been documented critical for many aspects of TGF␤ signaling, including cell proliferation and morphological transformation (Hocevar et al, 1999;Wilkes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The R-Smad/Smad4 complex subsequently translocates to the nucleus where it can function as a comodulator of transcription (Ten Dijke et al, 2002;Shi and Massagué, 2003). In addition to the aforementioned Smad-dependent pathways, Smad-independent responses have also been documented critical for many aspects of TGF␤ signaling, including cell proliferation and morphological transformation (Hocevar et al, 1999;Wilkes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The R-Smad/Smad4 complex subsequently translocates to the nucleus where it can function as a comodulator of transcription (Ten Dijke et al, 2002;Shi and Massagué, 2003). In addition to the aforementioned Smad-dependent pathways, Smad-independent responses have also been documented critical for many aspects of TGF␤ signaling, including cell proliferation and morphological transformation (Hocevar et al, 1999;Wilkes et al, 2003).Although the type I and type II TGF␤ receptors show a relatively homogeneous distribution over the cell surface of fibroblasts (Ehrlich et al, 2001;Yao et al, 2002), we have shown that both receptors localize to the basolateral domains in polarized epithelium (Murphy et al, 2004). Because basolateral trafficking for both receptors was independently regulated and mediated by sequences in the cytoplasmic tails of the receptors (Murphy et al, 2004), a further definition of the presumptive cis-acting element(s) was required.…”
mentioning
confidence: 99%
“…Although the canonical Smad pathway was shown not to be affected by PAK2 in fibroblasts (23), it remains unclear whether PAK2 has any effect in other types of cells. In the present study, we report that PAK2 restricts TGF-␤-elicited phosphorylation and transcriptional activities of R-Smads in madine-darby canine kidney (MDCK) epithelial cells.…”
mentioning
confidence: 99%
“…Several substrates of PAK2 have been identified in various contexts and mediate its wide range of cellular events, from cytoskeletal rearrangements to survival promotion and cellular transformation (19,22). Interestingly, PAK2 was reported to mediate TGF-␤ signaling in mesenchy-mal cells, but not in epithelial cells (23)(24)(25). The cell type-specific activation of PAK2 by TGF-␤ is controlled by the tumor suppressor Merlin and an epithelial-specific protein Erbin, both of which form a complex and inactivate PAK2 through blocking Cdc42/Rac1 binding in epithelial cells (26).…”
mentioning
confidence: 99%
“…It has also been shown that BMPs can regulate the development of human hematopoietic stem cells, presumably through the BMPactivated Smad proteins, Smad1 and Smad5, which they expressed in HSC (Bhatia et al, 1999). In addition, several Smad-independent pathways have been identified (Engel et al, 1999;Yue and Mulder, 2001;Wilkes et al, 2003). The TGF-b-activated receptor complex can signal through AKT, mitogen-activated protein kinases (MAPKs), the phoshoinositol-3-kinase (PI3K) and the PP2A/p70s65K pathways (Wakefield and Roberts, 2002).…”
Section: Smad Crosstalk Differential Effects Of Tgf-b Isoforms and Omentioning
confidence: 99%